The development of a guide to borderline orthodontic need - Ariane Sampson; Huw G. Jeremiah; Nicholas N. Lai; Robert Kirschen (SpringerOpen, 2022)
Abstract Objective To produce a guide for dentists and orthodontists to determine orthodontic treatment need in borderline cases (dental health component DHC 3) and to compare views of different panels of judges on treatment need. Materials and methods Prospective, observational study. Photographs of one hundred subjects displaying borderline occlusal traits (DHC3) were collected. Three panels of judges consisting of 25 orthodontists, 25 dentists and 25 lay persons assessed photographs based on orthodontic treatment need on aesthetic grounds. Results Spearman's correlation coefficient showed no statistical difference between the panels of judges (p < 0.001). The judges identified a 'high need' for treatment on aesthetic grounds for those with anterior open bites and reverse overjets. Kappa analysis showed moderate intra-rater agreement for the orthodontic and dental panels of judges (k = 0.47 and 0.45, respectively) and fair agreement (k = 0.26) for the lay panel, highlighting the intrinsic difficulty of assessing borderline malocclusions. Conclusion There was no statistical difference in the way the orthodontic, dental and lay panels of judges perceived treatment need for DHC 3 cases. Anterior open bites and reverse overjets were predominantly found to be in high need of treatment by all panels of judges. A 'Guide to Borderline Orthodontic Need' (GBON) is proposed consisting of 8 photographs of subjects with borderline occlusal traits (DHC3) determined unambiguously by lay, dental and orthodontic panels as either 'needing' or 'not needing' orthodontic treatment on aesthetic grounds. It is anticipated that this will assist users to make judgments on aesthetic grounds on the need for treatment in borderline cases.